Lot Feeding of Ostrich Growers Compared with Lucerne Silage Supplementation or Grazing on Pasture - Glatz, P.C.; Ru, Y.J.; Hastings, M.Y.; Black, D.; Rayner, B.; Miao, Z.H. (International Journal of Poultry Science, 2005)
Feed is a major cost in ostrich production. As a result there is interest in grazing ostriches on pasture or using silage to reduce feed costs and improve farm profitability. The purpose of this experiment was to conduct an on-farm trial to examine the performance of ostrich growers (49-78 kg liveweight) supplemented with lucerne silage or grazing on high quality pasture. This was compared with lot feeding of ostrich growers fed a commercial grower ration. There were 4 treatments imposed over a 6 week feeding trial; 1) birds fed 80% of their grower diet and allowed 3-5 hours/day of grazing on a lucerne-based pasture; 2) birds fed 80% of their grower diet and 1 kg of lucerne silage; 3) birds fed 50% of their grower diet and 1 kg of lucerne silage; and 4) control group fed a commercial grower feed in a feedlot. Birds fed 80% of the commercial grower diet with 3-5 hours/day grazing on the lucerne pasture or provided 1 kg lucerne silage as a supplement per day had similar (P>0.05) weight gain (14.15 and 14.40 kg respectively) as the control group (14.39 kg) over the 6 week experimental period. Birds fed on 50% of the grower diet with 1 kg of lucerne silage supplement had lower (P>0.05) weight gain (12.72 kg) over 6 weeks, but this was not significant. The results indicate that supplementing diets with lucerne silage or grazing on a lucerne based pasture can replace 20% of the grower diet without a negative effect on ostrich growth over a 6 week period.